The Influence of Brand Storytelling on Perceived Brand Authenticity with Brand Trust as a Mediating Variable on Gen Z Consumers at Kopi Tuku - Wulan Purnama Sari; Fiona CH Bernadett; Claribel Halim (Jurnal Komunikasi, 2025)
The development of modern marketing strategies requires brands to not only offer quality products but also convey value through strong narratives. Brand storytelling is becoming an increasingly important approach, especially in reaching Generation Z, a consumer group that grew up in the digital era, is critical of authenticity, and has high expectations for brand transparency. This study aims to examine how brand storytelling influences perceived brand authenticity by considering brand trust as a mediating variable. This study focuses on Generation Z consumers of Kopi Tuku, a local brand known for its inclusive narratives. A quantitative approach was used through a survey with a purposive sampling technique, involving respondents aged 18–28 who have consumed Kopi Tuku products. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method through SmartPLS software. Based on the results of the study, it can be concluded that brand storytelling has a positive and significant effect on brand trust and perceived brand authenticity among Generation Z consumers at Kopi Tuku. The analysis results show that a clear, consistent, and close-to-consumer brand narrative can increase consumer trust in the brand. This study also shows that brand trust acts as a partial mediator in the relationship between brand storytelling and perceived brand authenticity. This means that good storytelling not only directly shapes the perception of brand authenticity, but also works more powerfully by building consumer trust first.